68Ga-PSMA–Avid Small Cell Lung Cancer on PET/CT: Incidental Second Malignancy in Treated Prostate Cancer. (December 2020) - Sharma, Punit
Abstract : Abstract: 68 Ga–prostate-specific membrane antigen ( 68 Ga-PSMA) PET/CT has shown excellent results in imaging of prostate cancer. Some nonprostatic malignancies can also demonstrate 68 Ga-PSMA uptake, including primary lung adenocarcinoma. However, no such data are present for small cell lung cancer. We present the case of a 59-year-old man, where a second primary metastatic small cell lung cancer was discovered on 68 Ga-PSMA PET/CT done for suspected recurrence of prostate cancer.